2014
DOI: 10.1007/s00216-014-7624-z
|View full text |Cite
|
Sign up to set email alerts
|

p-Tolyl isocyanate derivatization for analysis of CWC-related polar degradation products by mass spectrometry

Abstract: Most of the precursors and/or degradation products related to the Chemical Weapons Convention (CWC) are polar. Identification of these molecules in environmental samples provides clues regarding the alleged usage and/or synthesis of the parent toxic chemicals. Such polar compounds need to be derivatized in order to analyze them by gas chromatography-mass spectrometry (GC-MS). In this study, we developed a new derivatizing reagent, para-tolyl isocyanate (PTI), for derivatization of polar CWC-related compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is important to notice that this is a common fragmentation pattern observed for plain, underivatized β-aminoethyl alcohols [21] as well as other derivatives of these such as their carbamates. [22] The molecular ion peak was observed for all derivatives as well, albeit present in very low abundance. Thus, the base peaks (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…It is important to notice that this is a common fragmentation pattern observed for plain, underivatized β-aminoethyl alcohols [21] as well as other derivatives of these such as their carbamates. [22] The molecular ion peak was observed for all derivatives as well, albeit present in very low abundance. Thus, the base peaks (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Through derivatization, the molecular weight of PA is significantly increased, and this results in an increased retention time in the GC column [6], although this is not accomplished with trimethylsilylation [11] as it was found that the retention time for the PA-TMS derivative was even shorter than PA itself (i.e., ~2.68 min vs. 5.32 min for PA). Another useful result that can be attained after a derivatization reaction is the generation of a product that exhibits sharper peaks relative to the starting, unmodified material as it is in the case of ethanolamines and phosphonic acids [31][32][33][34]. Our work is based on the use of 1,1′-carbonyldiimidazole (CDI), a versatile reagent that reacts with alcohols and amines to yield carbonates [35,36] and ureas, respectively [37][38][39][40], as well as carbamates when both species are used in a sequential fashion [41][42][43].…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…The non‐scheduled precursors/reaction products are one reaction step away from scheduled 1 and 2 chemicals of the CWC, in which phosphorus‐, sulfur‐, nitrogen‐, and/or arsenic‐containing moiety is still present. Detection of degradation/reaction products of some of the CWC‐scheduled chemicals has been reported previously 11–18 . In this comprehensive study, we have examined the reaction products of 2‐( N , N ‐dialkylamino)ethylchlorides with 2‐( N , N ‐dialkylamino)ethanols, which are the known precursors/degradation products of VX‐type compounds (VX compounds are potent nerve agents and the most lethal CWAs).…”
Section: Introductionmentioning
confidence: 99%